(untitled) (Gestión y Gerencia, 2023)
The efficiency and effectiveness in strategic financing and investment decisions is given by the correct application and control of investment projects, which ensure the carrying out of activities and works effectively based on quantifiable, verifiable criteria, in order to improve. In keeping with this convention, this article aims to develop the optimal financing structure for the photovoltaic park project using the profitability method based on cash flow. It is a quantitative and descriptive investigation through a comparative case study, several options are analyzed and evaluated to select the most convenient according to the available resources and the financial restrictions imposed, all of this inscribed in the superior objective of achieving the energy sovereignty of the nation. To propose financing strategies, for the use of resources in order to achieve the energy sovereignty of the province and the country in general.